Neurologic Complications in Infective Endocarditis: Identification, Management, and Impact on Cardiac Surgery. (October 2014) - Morris, Nicholas A.; Matiello, Marcelo; Lyons, Jennifer L.; Samuels, Martin A.
Neurologic complications of infective endocarditis (IE) are common and frequently life threatening. Neurologic events are not always obvious. The prediction and management of neurologic complications of IE are not easily approached algorithmically, and the impact they have on timing and ability to surgically repair or replace the affected valve often requires a painstaking evaluation and joint effort across multiple medical disciplines in order to achieve the best possible outcome. Although specific recommendations are always tailored to the individual patient, there are some guiding principles that can be used to help direct the decision-making process. Herein, we review the pathophysiology, epidemiology, manifestations, and diagnosis of neurological complications of IE and further consider the impact they have on clinical decision making.